2013
DOI: 10.1542/peds.2012-2789
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain in Infancy and Vascular Risk Factors in Later Childhood

Abstract: OBJECTIVE: We hypothesized that early weight gain would be associated with incident obesity, higher blood pressure, systemic inflammation, and arterial wall thickening in later childhood. METHODS: A longitudinal birth cohort was recruited antenatally from 2 maternity hospitals in Sydney, Australia, between September 1997 and December 1999. Three hundred ninety-five nondiabetic children who were followed to age 8 years had com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 29 publications
(25 reference statements)
7
53
0
5
Order By: Relevance
“…The study by Hof et al 21 shows that the magnitude of BMI at 9 months might be a useful measure in youth healthcare practice for identifying at a young age those children with increased risk for obesity and hypertension later in life. Likewise, Skilton et al 5 observed that early postnatal weight gain from birth to 18 months is independently associated with childhood overweight and obesity, excess central adiposity, and greater arterial wall thickness at 8 years of age. The present study collected a group of children born at term after a noncomplicated pregnancy and in the absence of perinatal illness.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study by Hof et al 21 shows that the magnitude of BMI at 9 months might be a useful measure in youth healthcare practice for identifying at a young age those children with increased risk for obesity and hypertension later in life. Likewise, Skilton et al 5 observed that early postnatal weight gain from birth to 18 months is independently associated with childhood overweight and obesity, excess central adiposity, and greater arterial wall thickness at 8 years of age. The present study collected a group of children born at term after a noncomplicated pregnancy and in the absence of perinatal illness.…”
Section: Discussionmentioning
confidence: 97%
“…2 More recent studies have shown that the postnatal growth pattern in infancy is also an important factor in the expression of later disease. [3][4][5][6] Indeed, it is a matter of great interest to know how the interaction between pre-and postnatal growth affects the development of cardiometabolic risk factors.…”
mentioning
confidence: 99%
“…In fact, the loci that contribute genetic susceptibility to obesity play a dominant role in regulating weight and fat mass in the first three years of life but do not appear to affect birth weight (74). Weight gain in infancy is a risk factor for elevated CRP and great carotid intima-media thickness in non-diabetic children (75). Large cohort studies have identified surprising links between infant growth and inflammatory diseases such as type 1 diabetes (76) and asthma (77), suggesting that early rapid growth rates may have broad effects on inflammatory responses to environmental stimuli during childhood.…”
Section: What Are the Initiators Of Metainflammation?mentioning
confidence: 99%
“…В последние годы появились данные о влиянии высокой скорости роста в младенчестве на состояние здоровья ребенка в стар-шем возрасте, а также на состояние здоровья взрос-лого. По данным M. Skilton и соавт., у детей с высокой скоростью роста в первые 2 года жизни отмечалось повышение ИМТ, более высокий уровень артериального давления и увеличение плотности сосудов в возрасте 8 лет [6]. Аналогичное исследование было проведено в Швеции.…”
Section: Introductionunclassified